Satisfaction with amplification in daily life (SADL) in monaural and binaural hearing aid users - Zulkefli, Amirah Amalina; Wan Ahmad, Wan Aslynn Salwani (IIUM Press, 2018)
Introduction: This study was aimed to identify the level of satisfaction in monaural and binaural hearing aid users by using Malay Satisfaction of Amplification in Daily Life (SADL) questionnaire (Ramli, 2017).